Impact of Psychiatric Illnesses and Selective Serotonin Reuptake Inhibitor Medications on Baseline Neurocognitive Testing. (19th October 2021) - Asfaw, Zerubabbel K; Hannah, Theodore C; Ali, Muhammad; Li, Adam Y; Spiera, Zachary; Marayati, Naoum Fares; Kalagara, Roshini; Dreher, Nickolas; Schupper, Alexander J; Gometz, Alex; Lovell, Mark R; Choudhri, Tanvir
Abstract: Introduction: Neurocognitive tests are an integral component of sport-related concussion (SRC) workup. A history of psychiatric illness (HPI) is common among young athletes. Investigations of factors that influence athletes' baseline neurocognitive function are crucial for an accurate assessment of SRC. Objective: In this study, we aim to elucidate the effect of HPI and selective-serotonin reuptake inhibitor (SSRI) medication use on baseline neurocognitive performance in young athletes. Methods: We conducted a retrospective cross-sectional study of Immediate Post-Concussion Assessment and Cognitive Testing assessments. A total of 268 athletes with HPI and a control group of 6, 364 athletes were included. The outcomes were total symptom score based on post-concussion symptom scale, verbal memory, visual memory, visual motor, reaction time, and impulse control scores with self-reported HPI status and SSRI use. Results: Athletes with HPI had an elevated symptom score in both univariate analysis ( p  < .0001) and multivariate analysis ( p  < .0001). HPI influence on visual memory score was not robust to multivariate analysis ( p  = .24). Athletes with HPI who reported SSRI medication use had the same baseline neurocognitive performance as other athletes with HPI. HPI influences athletes' baseline neurocognitive performance by elevating symptom scores. HPI does not alter any of the objective neurocognitive composite scores in contrast to previous work. Conclusions: Clinicians should consider the impact of HPI on baseline neurocognitive performance during the assessment of a suspected SRC. Additional research is required to bolster our findings on SSRI use and ascertain the effects of other drug classes on baseline neurocognitive performance.